2011
DOI: 10.1017/s2078633611000063
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis and subpopulation characterization of Ripollesa sheep breed

Abstract: The Ripollesa sheep breed is an important Spanish local breed mainly located in the Mediterranean mountains and cultivated plains of Catalonia, exploited under semi-extensive production systems and currently intended for meat production. The morphological characterization of the Ripollesa breed was carried out from the study of eight flocks representative of different subpopulations. A total of 224 Ripollesa ewes and 17 rams were recorded for their live weight and 12 morphological measures, which were used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 9 publications
0
26
1
1
Order By: Relevance
“…This breed is a representative example of the meat-type sheep industry from the Mediterranean basin, the 'pascual'-type lamb being its typical commercial product (22 to 24 kg of live BW at slaughter). Ripollesa individuals have dark brown or black marks on the head and legs, and white semi-fine wool with closed fleece (Esquivelzeta et al, 2011). This research focused on the age at first lambing (AFL) defined as the number of days between the ewe's birth date and the date of its first lambing.…”
Section: Methodsmentioning
confidence: 99%
“…This breed is a representative example of the meat-type sheep industry from the Mediterranean basin, the 'pascual'-type lamb being its typical commercial product (22 to 24 kg of live BW at slaughter). Ripollesa individuals have dark brown or black marks on the head and legs, and white semi-fine wool with closed fleece (Esquivelzeta et al, 2011). This research focused on the age at first lambing (AFL) defined as the number of days between the ewe's birth date and the date of its first lambing.…”
Section: Methodsmentioning
confidence: 99%
“…Among the native sheep breeds in Spain, the Ripollesa is the most abundant breed in Catalonia (i.e., the northeastern region of Spain), producing pascual-type lambs that are slaughtered at ∼3 mo of age with a carcass weight of 13-16 kg. It is a rustic meat-type breed with convex profile, characteristic black or dark brown pigmentation on the head and legs, and white entrefino-type wool (Esquivelzeta et al 2011). The meat-type Lacaune is the most numerous sheep breed in France for producing lambs, with a census exceeding 300 000 ewes (Perret et al 1995).…”
Section: Animals and Managementmentioning
confidence: 99%
“…Males are generally larger than females for several morphometric traits of ovine breeds (Esquivelzeta et al (2011) and Mavule et al (2013)); however, females seem to be higher especially for rump width as can be observed in Esquivelzeta et al (2011) in Ripollesa breed. It is possible that after 240 days, more differences between the sexes will become evident, as Costa Júnior et al (2006) found sexual dimorphism in Santa Ines sheep for other traits.…”
Section: Morphometric Traitsmentioning
confidence: 80%